Implementasi Kombinasi Model PBL, NHT, dan Make A Match untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa pada Pembelajaran IPS - Saleh, Muhammad (Universitas Nusantara PGRI Kediri, 2021)
The problem in this study is the low level of student learning activities so that it has an impact on student learning outcomes in social studies learning. The purpose of this study was to describe teacher activities, describe student activities and analyze student learning outcomes. This study used a qualitative research approach with the type of classroom action research, which was carried out in 2 cycles of 4 meetings. The subjects of this study were students of class VA at SDN Teluk Tiram 1 Banjarmasin in the academic year 2020/2021, the number of students was 11 students consisting of 2 male students and 9 female students. The types of data in this study are qualitative data and quantitative data. Qualitative data obtained through observation of teacher and student activities. While quantitative data obtained through student learning outcomes. The results of this study indicate that the teacher's activities at meeting 4 reached the